Analisis Prospek Usaha Tanaman Hias Kota Mataram (Studi Kasus UD. Yuka Collection) - Pande Komang Suparyana; Endah Wahyuningsih; Wendi Hasyim; Dudi Septiadi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Ornamental plants are not only a hobby, but also a commodity with a high economic value. This is in line with the increasing demand for ornamental plants at home and abroad. High demand is certainly an opportunity for cultivators who choose to make ornamental plants as an economic activity. This study aims to analyze the costs incurred and the income generated in the ornamental plant business in the city of Mataram. The ornamental plant business observed in the case study of this research is in UD. Yuka Collection. The data analysis in this research are cost, income, and R/C ratio analysis. The results showed that the income earned by UD. Yuka Collection for the period April-May 2022 from the ornamental plant business is Rp. 91,942,053,51. The value of business efficiency obtained shows a number greater than one, or equal to 1.5125. This shows that the business run by UD. Yuka Collection has been efficient and deserves to be developed.